Relationship between Foreign Loans and Economic Growth in Nigeri - Akeem, Lawal Babatunde; John, Dada; Kehinde, Ajose; Grace, Aina (IJRDO - Journal of Business Management, 2017)
The relationship between foreign loans and economic development of underdeveloped countries is still questionable and debatable, hence the purpose of this study is to examine the relationship between foreign loans and growth of Nigerian economy over the year for 35 years. Data’s used was obtained from Bureau of Statistics and related journals for the period of 1980 to 2015. In order to analyze the data, both econometric and statistical methods were used. The economic regression model of ordinary least square (OLS) was applied in evaluating the relationship between foreign loans and economic development in Nigeria. The result revealed that foreign loans have no significant impact on economic growth in Nigeria. However, the study recommended that Nigerian government should promote exportation of domestic products as a high exchange rate will make our goods more attractive in the foreign market and thus, will increase foreign exchange earnings. Furthermore, Nigeria’s external debt should adequately keep track of the debt payment obligations and the debt should not be allowed to pass a maximum limit so as to avoid debt overhang.